Down‐phase auditory stimulation is not able to counteract pharmacologically or physiologically increased sleep depth in traumatic brain injury rats. (26th April 2022) - Moreira, Carlos G.; Hofmann, Pascal; Müllner, Adrian; Baumann, Christian R.; Ginde, Varun R.; Kollarik, Sedef; Morawska, Marta M.; Noain, Daniela
Summary: Modulation of slow‐wave activity, either via pharmacological sleep induction by administering sodium oxybate or sleep restriction followed by a strong dissipation of sleep pressure, has been associated with preserved posttraumatic cognition and reduced diffuse axonal injury in traumatic brain injury rats. Although these classical strategies provided promising preclinical results, they lacked the specificity and/or translatability needed to move forward into clinical applications. Therefore, we recently developed and implemented a rodent auditory stimulation method that is a scalable, less invasive and clinically meaningful approach to modulate slow‐wave activity by targeting a particular phase of slow waves. Here, we assessed the feasibility of down‐phase targeted auditory stimulation of slow waves and evaluated its comparative modulatory strength in relation to the previously employed slow‐wave activity modulators in our rat model of traumatic brain injury. Our results indicate that, in spite of effectively reducing slow‐wave activity in both healthy and traumatic brain injury rats via down‐phase targeted stimulation, this method was not sufficiently strong to counteract the boost in slow‐wave activity associated with classical modulators, nor to alter concomitant posttraumatic outcomes. Therefore, the usefulness and effectiveness of auditory stimulation as potential standalone therapeutic strategy in the context of traumatic brain injury warrants further exploration.